Prevalence and Risk Factors of Gastric Adenoma and Gastric Cancer in Colorectal Cancer Patients - Dae Hyun Tak; Hee Seok Moon; Sun Hyung Kang; Jae Kyu Sung; Hyun Yong Jeong (Gastroenterology Research and Practice)
Background/Aims. To evaluate the incidence of gastric adenoma and gastric cancer in colorectal cancer patients, as well as the clinicopathological features that affect their incidence. Methods. Among patients who underwent surgery after being diagnosed with colorectal cancer between January 2004 and December 2013 at Chungnam National University Hospital, 142 patients who underwent follow-up upper gastrointestinal endoscopy were assigned to the patient group. The control group included 426 subjects randomly selected. The patient group was subdivided into two: one that developed gastric adenoma or cancer and one that did not. Clinicopathological characteristics were compared between these groups. Results. In total, 35 (24.6%) colorectal cancer patients developed a gastric adenoma or gastric cancer, which was higher than the number in the control group (20 [4.7%] patients; p<0.001). Age, alcohol history, and differentiation of colorectal cancer were associated with higher risks of gastric adenoma or gastric cancer, with odds ratios of 1.062, 6.506, and 5.901, respectively. Conclusions. In colorectal cancer patients, screening with upper gastrointestinal endoscopy is important, even if no lesions are noted in the upper gastrointestinal tract at colorectal cancer diagnosis. Endoscopic screening is particularly important with increasing age, history of alcohol consumption, and poor cancer differentiation.